THE EFFECTS OF LEARNING START WITH QUESTIONS (LSQ) STRATEGY AND STUDYING MOTIVATION TOWARD STUDENTS’ ACHIEVEMENT - Ardison Ardison (English Language Teaching and Research, 2018)
This research was motivated by the research results and journal (Wahyudin :2008, Meidina :2014, dan Irsadi:2015), also interviews the researcher has done. The observation and interview results indicated that students’ achievement in studying hasn't yet been one as expected. This situation was preconceived that there was bearing with learning strategy that was utilized by educator and students’ motivation itself. Based on the research result and journal, it’s stated that learning strategy and studying motivation have significant impact to the students’ achievement in studying, either separately or integratively.Concerning with the problem and research objectives, the approach used in this research was experimental approach by comparing the students’ achievement of experimental class to the control class. The population of this research was all students of XI Social Class at MAN Koto Baru Solok, 2015 / 2016 academic year containing 83 students and total sample members were 54 students selected by using cluster random sampling technigue. The instrument was questionnaires , objectives test, and the observation form. To determine the effects among variables, the researcher used the analysis technigues of F test and ANOVA by using program of SPSS 16.0.The research result showed that: (1) students who were taught by using LSQ, they had a higher achievement than other, with significance level Fcomputing = 2.450 > F table = 2.10. It could be concluded that LSQ strategy have effect towards students’ achievement. (2) the students who had high motivation in learning process were showed that they got good result, with significance level Fcomputing = 3.687 > Ftable = 2.10. Its mean that motivation have impact towards students’ achievement. ( 3) the students who had low motivation was taught by LSQ were showed that they got good result, with significance level Fcomputing =976> F table =2.10. Its mean that the strategy had effect to the students’ achievement. (4) there were interaction between LSQ and motivation in learning towards English language achievement with significance level Fcomputing = 537 >F table = 2.10. Its mean that between strategy and motivation in learning, has given impact each other. The last one, the students’ activities in experimental class more active than control.. Based on the result of this study, it concludes that the use of LSQ strategy and motivation successfuly effects towards students’ achievment of MAN Koto Baru Solok grade XI Social. Key word: Learning Starts with Questions, Motivation , achievement.